HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN IBU DALAM MENGHADAPI KEHAMILAN TRIMESTER III DI PUSKESMAS TEGALSIWALAN: The Correlation between Family Support and Mother's Anxiety Level in Facing Third Trimester Pregnancy at the Tegalsiwalan Health Center - Karimatul Hasanah (Forind Press, 2024)
Mothers who experience anxiety need family support in dealing with pregnancy in the third trimester of pregnancy, with family support it turns out that it is also able to reduce anxiety in pregnant women. This study aims to determine the relationship between family support and the level of maternal anxiety in facing the third-trimester of pregnancy at the Tegalsiwalan Health Center. This study discussed and processed data based on the results of a survey on pregnant women at the Tegalsiwalan Health Center with a total sample of 30 pregnant women with 83% not anxious and 17% Data analysis techniques use correlation tests and validity scales. Research analysis using Wilcoxon obtained significant data of p = 0.000 so that p = 0.000 <α = 0.05, the results of H1 were accepted, namely that there was a correlation between family support and the level of anxiety of pregnant women in dealing with third-trimester pregnancy at the Tegalsiwalan Health Center, the level of anxiety had decreased. after the researchers carried out socialization by motivating pregnant women from families with informative support, real support, giving attention, giving warmth, giving affection and protection both internally and externally, while the level of anxiety was cognitive and behavioral so that they did not experience anxiety in dealing with third-trimester pregnancy at the Tegalsiwalan Health Center. So family support for pregnant women is very important so they don't experience anxiety levels.